PENDAMPINGAN PRAKTEK PEMBUKUAN AKUNTANSI MENGGUNAKAN APLIKASI RANDU POS & AKUTANSI UKM PERABOTAN NASYWA DI JAKARTA SELATAN: Assistance in Accounting Bookkeeping Practice Using the Randu Pos Application & Nasywa Furniture SME Accounting in South Jakarta - Firmansyah, Muhammad; Putra, Surya Dwi; Herdinov, Adam; Abiyah, Indra Adib; Rahmadi, Zara Tania; Wahyudi, Muhammad Aria (PUAN INDONESIA, 2024)
This study evaluated the impact of bookkeeping assistance using the Randu Pos application on furniture SMEs in South Jakarta. The results noted improved efficiency in daily record-keeping and sales processes, as well as significant accuracy of financial data. The mentoring also successfully improved furniture stock management, reducing human error. Despite initial challenges, the SME owners experienced immediate benefits, while the trainees developed practical skills. Recommendations for further training were made based on the positive feedback. Overall, the mentoring contributed to the efficiency and accuracy of furniture SME bookkeeping in the digital age. Assistance in accounting bookkeeping practices using the Randu Pos application and furniture SME accounting can help improve efficiency and accuracy in the financial recording of furniture SMEs.